Penerapan Algoritma Bee Colony Untuk Optimasi Rute Tempat Wisata Kuliner Di Bandung - Randi Teguh Waluya Nugraha (JURIKOM (Jurnal Riset Komputer), 2018)
Bandung is a city that has a culinary tour is very interesting and many, even not infrequently tourists from outside the  city was looking for culinary in the city of flowers. But because of the extent of his city Bandung it needed an optimization system that can help culinary lovers to find the shortest route. The path with the shortest distance will be selected as the preferred pat. Bee Colony`s algorithm is capable of solving the shortest route problem because it has the optimization capability efficiently. The results obtained in this study is the best solution in determining the shortest path to find a culinary place without having to waste time on the road.